(untitled) (Research, Society and Development, 2022)
Brazil occupies the first place in the world in terrestrial biodiversity, sheltering about 200,000 native plant species, which it is estimated that at least half have some therapeutic property. From this perspective, in the current situation, natural alternative therapies have had a growing panorama, given the various benefits of this practice, such as less toxicity, greater biocompatibility and more affordable cost. Among the various existing plant species, Rhaphiodon echinus, an endemic herb native to Brazil included in the Lamiaceae family, stands out for its performance in pharmacological activities. Therefore, the objective of this review is to discuss the ethnobotanical, phytochemical and pharmacological properties of this plant species. For this, a search of the literature published between 2011 and 2021 in the online databases National Libary of Medicine (PubMed), Academic Google, Institutional Repository of UNESP; Hoehnea- Institute of Botany; UFPR’s Digital Collection; Scientific Archive and Pharmaceutical Biology Magazine. After analyzing the data found in the literature, following the established inclusion criteria, it was found that Rhaphiodon echinus is a promising species for the drug industry, as it has photoprotective action, antifungal activity against Candida tropicalis strains, in addition to potential antioxidant, anti-inflammatory and antifungal when used to treat oral thrush and digestive tract disorders. Also, when associated with antimicrobials against strains of some fungal and bacterial species, Rhaphiodon echinus has higher anti-cabterian and antifungal activity, suggesting a synergistic effect. However, more methodologically structured studies need to be carried out to better elucidate its broad therapeutic potential.